2014
DOI: 10.1021/pr500064m
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Comparison of 3D and 2D Glioma Models Reveals Increased HLA-E Expression in 3D Models is Associated with Resistance to NK Cell-Mediated Cytotoxicity

Abstract: Three-dimensional cell culture techniques can better reflect the in vivo characteristics of tumor cells compared with traditional monolayer cultures. Compared with their 2D counterparts, 3D-cultured tumor cells showed enhanced resistance to the cytotoxic T cell-mediated immune response. However, it remains unclear whether 3D-cultured tumor cells have an enhanced resistance to NK cell cytotoxicity. In this study, a total of 363 differentially expressed proteins were identified between the 2D- and 3D-cultured U2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…He et al . also reported global proteomic comparisons of 2D- and 3D-cultured cells using glioma U25l cells, which also showed the enrichment of glycolysis-associated terms in 3D-up-regulated proteins 15 . This proteomic study identified seven oxidative phosphorylation-associated proteins that were down-regulated in 3D culture (AHCY, ATP5A1, ATP5F1, COX4I1, UQCRC1, UQCRC2, and PPA1).…”
Section: Resultsmentioning
confidence: 87%
“…He et al . also reported global proteomic comparisons of 2D- and 3D-cultured cells using glioma U25l cells, which also showed the enrichment of glycolysis-associated terms in 3D-up-regulated proteins 15 . This proteomic study identified seven oxidative phosphorylation-associated proteins that were down-regulated in 3D culture (AHCY, ATP5A1, ATP5F1, COX4I1, UQCRC1, UQCRC2, and PPA1).…”
Section: Resultsmentioning
confidence: 87%
“…found in tumors often heighten resistance to radiotherapy and chemotherapy [80][81][82]. Glioblastoma spheroids harbor hypoxic cores where metabolic pathways, including those involving lipids, are changed [4,[83][84][85].…”
Section: Discussionmentioning
confidence: 99%
“…However, this result was attributed to a decrease in heat shock protein 70 (HSP70) expression and associated defective tumor antigen presentation 45 . Glioma spheroids also appeared to have an increased resistance to natural killer (NK) cell cytotoxicity compared to glioma cells grown in 2D monolayers 46 . These findings support the importance of using 3D culture for developing in vitro models of tumor-immune cell interactions.…”
Section: Biomaterials To Create 3d Tumor Modelsmentioning
confidence: 99%